2012
DOI: 10.1002/qua.24314
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the dissolution of Mn ions from LiMn2O4 cathode in the application of lithium ion batteries: First principle molecular orbital method

Abstract: The dissolution phenomenon of Mn ions in LiMn 2 O 4 (LMO) cathode material for lithium ion batteries (LIBs) was investigated by a first principle calculation using the discrete variational Xa molecular orbital method. It was found that the oxidation number of Mn ions easily increases at high temperatures due to the empty levels of Mn 3d orbitals located in the vicinity of the Fermi energy level of LMO crystal. The changes of density of states (DOS) and Mn-O bonding properties with doping were examined. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…The Mn dissolution is also affected by the electronic property of Mn, as previous studies have reported. [ 23,57–60 ] The electronic orbital configuration for oxidation of Mn 3+ is depicted in Figure 5A. The electronic configuration of Mn 3+ has three electrons in the t 2g orbital and one electron in the e g orbital.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Mn dissolution is also affected by the electronic property of Mn, as previous studies have reported. [ 23,57–60 ] The electronic orbital configuration for oxidation of Mn 3+ is depicted in Figure 5A. The electronic configuration of Mn 3+ has three electrons in the t 2g orbital and one electron in the e g orbital.…”
Section: Resultsmentioning
confidence: 99%
“…From the summation of all COOP values under the Fermi energy, which was an indicator of the covalent character of a chemical bonding. [ 23 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method does not use the pseudopotential approximation. All the atomic orbitals of the model cluster are included in the calculation, which can provide reliable information on the molecular orbitals and electron distributions …”
Section: Methodsmentioning
confidence: 99%
“…It is reported that substitution of Mn ions with other metals such as Mg, Al, Cr, Co, Ni, Zn, Mg, Ga slows dissolution of Mn into the electrolyte [4]. Partial replacing Mn, could increase the average valence of Mn in LiMn 2 O 4 (decreasing the Mn 3+ in LiMn 2 O 4 ), and could supress the Jahn-Teller eect [5]. The present work is focused on the understanding of bication eect of (Cr 3+ and V 5+ ) substituted on LiMn 2 O 4 cathode in addressing the hampering issues that are concerned with the unacceptable capacity fade and the poor cycle life behavior of spinel cathode.…”
Section: Introductionmentioning
confidence: 99%